Comment on ‘A Wealth Based Explanation for Earnings Conservatism’ - Benninga, Simon (Review of Finance, 2001)
Comment on ‘A Wealth Based Explanation for Earnings Conservatism’ Get access Simon Benninga Simon Benninga Search for other works by this author on: Oxford Academic Google Scholar Review of Finance, Volume 5, Issue 3, 2001, Pages 351–352, https://doi.org/10.1023/A:1013834904395 Published: 01 December 2001